PENGARUH PROFITABILITAS, STRUKTUR AKTIVA DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (Students' Journal of Accounting and Banking, 2014)
This study aims to determine the effect of profitability, asset structure and size of the Company's Capital Structure on Manufacturing Companies Listed in Indonesia Stock Exchange (IDX). The population in this study is a manufacturing company that is listed on the Indonesia Stock Exchange 2010-2012. The samples in this study were taken by purposive sampling method. Data were analyzed by using the skewness-kurtosis test for normality, the classical assumption, koofisiendeterminasi test, F-test and test hypotheses. The results of this study are significant negative effect on the profitability of capital structure, asset structure is not a significant negative effect on the capital structure, the size of the company significant positive effect on the capital structure.Keywords: capital structure, profitability, asset structure, size of the Company